Brasil-Venezuela: Evoluç\~ao das relaç\~oes bilaterais e implicaç\~oes da crise venezuelana para a inserç\~ao regional brasileira (1999-2021) - Pedro Silva Barros; Raphael Camargo Lima; Helitton Christoffer Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This Discussion Paper addresses the recent history and dynamics of relations between Brazil and Venezuela from the political-diplomatic, economic-commercial and security and defense dimensions. The study analyses decades of advances and setbacks in bilateral understandings between both countries up to the most recent consequences of the Venezuelan crisis and its impacts on South American governance. In the past twenty years, economic relations between Brazil and Venezuela was structured around bilateral trade with a large surplus with Brazil, financing the export of engineering goods and services, investments in infrastructure and the energy partnership between the two countries. The article addresses exceptional circumstances on the Roraima and Amazonas in bilateral relations, the use of financial instruments to facilitate trade exchanges in the region, the geoeconomic impacts on bilateral trade due to economic sanctions suffered by Venezuela, the recent migration of Venezuelans for Brazil. The study also presents other strategic issues such as military cooperation between Brazil and Venezuela, the regional security and defense architecture, the central role of regional integration in multilateral relations and the potential for energy cooperation.
Keywords: F14; F15; F51; F52; 330; relations Brazil-Venezuela; crisis; regional integration; bilateral trade